1991
DOI: 10.1177/004051759106100503
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Yarn Tension in Air-Jet Filling Insertion

Abstract: Yarn tension during air-jet filling insertion is analyzed experimentally and theo retically for drum and loop storage systems. In the case of drum storage, yarn tension is higher and more even. The model for drum storage shows that the yarn tension depends on the frictional force between the drum surface and the yarn, the mass linear density of the yam, and the unwinding speed. A set-up is developed for air friction coefficient measurements, and friction coefficients for two different yarns are deter mined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Uno 1 derived the equations of motion of air jet weft insertion utilizing empirical relations to determine the air flow velocity and the air friction coefficient. Adanur and Mohamed 2,3 derived theoretical models for yarn motion and tension in drum and loop-storage systems for air jet insertion. They presented a numerical technique to solve the equations of motion for the yarn and to calculate the resulting yarn velocity.…”
mentioning
confidence: 99%
“…Uno 1 derived the equations of motion of air jet weft insertion utilizing empirical relations to determine the air flow velocity and the air friction coefficient. Adanur and Mohamed 2,3 derived theoretical models for yarn motion and tension in drum and loop-storage systems for air jet insertion. They presented a numerical technique to solve the equations of motion for the yarn and to calculate the resulting yarn velocity.…”
mentioning
confidence: 99%
“…Celik et al 4 incorporated the flow from the relay nozzles into an analogous model by using time and place factors for the different forces acting on the yarn. Nosraty et al 5 used the model from Adanur and Mohamed 3 as a basis for their model to analyse the influence of yarn count and air supply pressure on weft yarn tension. Szabó et al 6 established a similar methodology for confusor guide systems.…”
Section: Several Models and Simulation Methodologies Aimed At Modellimentioning
confidence: 99%
“…2 opted for a very similar approach for yarn insertion through a (slotted) tube. Adanur and Mohamed 3 also adopted these methods to calculate the yarn tension during yarn unwinding from drum and loop storage systems. Celik et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It increased with time (distance constant) and decreased with distance from the nozzle. Adanur and Mohamed [6] also analyzed yarn tension during air-jet filling insertion both experimentally and numerically for drum and loop storage systems. The model for drum storage showed that the yarn tension depended on the frictional force between the drum surface and the yarn, the mass linear density of the yarn, and the unwinding speed.…”
Section: Air Jet Weft Insertionmentioning
confidence: 99%